Long non-coding RNA-polycomb intimate rendezvous - Cerase, Andrea; Tartaglia, Gian Gaetano (Open biology, 2020)
The interaction between polycomb-repressive complexes 1/2 (PRC1/2) and long non-coding RNA (lncRNA), such as the X inactive specific transcript Xist and the HOX transcript antisense RNA (HOTAIR), has been the subject of intense debate. While cross-linking, immuno-precipitation and super-resolution microscopy argue against direct interaction of Polycomb with some lncRNAs, there is increasing evidence supporting the ability of both PRC1 and PRC2 to functionally associate with RNA. Recent data indicate that these interactions are in most cases spurious, but nonetheless crucial for a number of cellular activities. In this review, we suggest that while PRC1/2 recruitment by HOTAIR might be direct, in the case of Xist , it might occur indirectly and, at least in part, through the process of liquid–liquid phase separation. We present recent models of lncRNA-mediated PRC1/2 recruitment to their targets and describe potential RNA-mediated roles in the three-dimensional organization of the nucleus.